2019
DOI: 10.3314/mmj.19.002
|View full text |Cite
|
Sign up to set email alerts
|

Endangered Zoonotic Fungal Species from Chicken (<i>Gallus gallus domestics</i>)

Abstract: Lophophyton gallinae (Microsporum gallinae) is a zoophilic fungus that causes ringworm in chickens and related species, and occasionally in humans. There are 45 human cases worldwide including a Japanese case from Okinawa in 2009. After the finding of the human L. gallinae case, 793 chickens in Japan, including 293 from the mainland and 500 from the Nansei Island areas, were investigated to determine the prevalence of dermatophytes and their related fungal species. The survey was carried out from December 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Another zoophilic dermatophyte that may cause rare human infections is L. gallinae. The elective hosts of this dermatophyte are chicken, with sporadic cases in other animals and humans (Londero et al, 1969;Yamaguchi, 2019). Among the few reported human infections, predisposing conditions such as diabetes or immunosuppressive diseases were observed in several cases (del Palacio et al, 1992;Poblete-Gutiérrez et al, 2006).…”
Section: Rural Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Another zoophilic dermatophyte that may cause rare human infections is L. gallinae. The elective hosts of this dermatophyte are chicken, with sporadic cases in other animals and humans (Londero et al, 1969;Yamaguchi, 2019). Among the few reported human infections, predisposing conditions such as diabetes or immunosuppressive diseases were observed in several cases (del Palacio et al, 1992;Poblete-Gutiérrez et al, 2006).…”
Section: Rural Areasmentioning
confidence: 99%
“…The fungus' endemicity is, however, in doubt since it has been reported from several countries worldwide, including Brazil, the United States, France, Belgium, Iran, and Saudi Arabia (Beguin et al, 2013). Outside the Indian subcontinent, Chabasse (1988) found the fungus in the soil in France and it was isolated from monkeys in Argentina (Boehringer et al, 1998) and Japan (Yamaguchi, 2019).…”
Section: Wild Animalsmentioning
confidence: 99%
“…Trichophyton terrestre , recovered from 12 specimens in the present study, has been reported to be isolated as an anamorph or in the perfect state Arthroderma quadrifidum from several bird species, many of which are waterfowl [ 9 ], but also from Ph. colchicus [ 6 ], from G. gallus domesticus in Japan [ 27 , 28 , 29 ] and to a lesser extent in Germany [ 10 ]. This fungal species is considered as uncommon on birds’ feathers, probably for its sensitivity to feathers’ fat and maybe to sunlight, and is reported to be recovered when it was the only fungal species [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nweze [4] found the prevalence of fungal skin diseases was 18.2% in chickens and 13.6% in ducks, with M. gallinae isolated from 75% of infected chickens and 100% of infected ducks. M. gallinae has also been reported to infect dogs, monkeys, cats, squirrels, mice, canaries, pigeons, and turkeys, as well as causing ringworm in humans, and severe infections in immunocompromised hosts [5,6].…”
Section: Introductionmentioning
confidence: 99%